Recycling some byproducts for fabrication of green cement with good mechanical strength and high efficiency for wastewater treatment - Fatma M. Helmy; S.M.A. El-Gamal; M. Ramadan; F. A. Selim (Scientific Reports)
Abstract This research aims to produce green cement, as an alternative to traditional cement, with outstanding performance. Five alkali-activated cement pastes were fabricated based on NaOH-activation of slag (GGBFS), bypass (B), and/or silica fume (S). Codes of five pastes are C, C-20B, C-30B, C-10B10S, and C-20B10S, as C is the control paste containing 100% slag. The compressive strength of the fabricated pastes was measured at different curing regimes: Conventional curing for 3 months and autoclave curing at 4 bar/153◦C, 7 bar/178◦C, and 10 bar/198◦C for 4 h. XRD, TGA/DTG, SEM/EDX, and BET/BJH techniques were utilized to clarify the phase development, morphological and texture features of the formed alkali-activated composite pastes. Besides, the removal capacity of some pastes for methylene blue and indigo-carmine dyes from aqueous media was evaluated. The results confirmed that C and C10B10S (80%GGBFS + 10%B + 10%S) pastes have significant mechanical properties and distinctive meso-porosity that can remove both anionic and cationic dyes.